Estudo comparativo dos efeitos cardiovasculares dos monoterpenos acetato, butirato e isobutirato de nerila em ratos - Carvalho, Emanuella Feitosa de (2019)
Structurally similar compounds such as neryl acetate (NA), neryl isobutyrate (NI) and neryl butyrate (NB) - acyclic monoterpene esters - are substances of plant origin with no activity described in the cardiovascular system of rats. Studies show that the structural conformation and the presence of a certain functional grouping may interfere in the pharmacological potency of chemical analogues. Thus, our objective was to characterize the pharmacological effects of these esters on cardiovascular parameters in vivo and in isolated preparations of the thoracic aorta and right atrium of rats. Isometric contractions of aortic and rhythmic atrium rings, as well as recording of mean arterial pressure and heart rate were obtained through a data acquisition system. NB (0.001-2000 μM) induced a greater contractile effect on aortic rings with intact endothelium when compared to NA or NI (1-2000 μM), with Emax of 45.0% ± 6.27% in the highest concentration. In endothelium denuded aortic rings, NB presented 81.45% ± 7.70% Emax in the concentration of 30 μM, different from the magnitude achieved by NI or NA with 2000 μM (25.54% ± 8.35% and 6.51% ± 1.80%, respectively). Pretreatment of intact endothelium aortic rings with nitric oxide-guanylyl cyclase inhibitors (L-NAME or ODQ) potentiated the contractile effect of NB, unrecorded activity in the presence of the cyclooxygenase inhibitor (INDO). α-adrenergic receptor antagonists (prazosin and yohimbine), but not the thromboxane prostanoid receptor (seratrodast), reversed NB-induced contractions (30 nM). The contraction induzed by NB was attenuated in the presence of the phospholipase C inhibitor (U-73122), Rho-kinase (Y-27632), CaV (verapamil) or Ca2+ free calcium condition. In contrast, NA presented a vasodilatory effect on the reversal of contractile smooth muscle agents, such as KCl, phenylephrine or U-46619. In the rings with intact endothelium the KCl reversal was more expressive, with EC50 of 280.0 [193.3-405.6] μM. Pretreatment with L-NAME, methylene blue or ODQ attenuated the vasorelaxant effect of AN, while the presence of prostaglandin inhibitors (INDO), potassium channel (TEA) or PKA (H-89) did not alter this effect. Concentration-effect curves for the orthovanadate or phorbol ester were not displaced in the presence of NA (600 μM). NA and NB induced bradycardia in isolated preparations of the right atrium. In vivo NB induced hypotension and bradycardia and NA induced bradycardia only in the isolated preparations, whereas NI did not alter heart rate. The hypotensive effect of NB was significant in relation to NA in the highest doses. In conclusion, NB has vasoconstrictor properties modulated by the endothelium in rat isolated aorta, an effect probably mediated by the recruitment of α-adrenergic receptors. No vasopressor effect was seen in vivo, suggesting that NB may exert another. On the other hand, NA presents a vasorelaxant effect with a probable participation of the nitric oxide-guanylyl cyclase pathway and bradycardia in the isolated atrium. NI was inert in the different types of preparations studied. Although chemically similar, the studied substances presented profiles of different responses, probably related to differences in structure and conformation of the molecules.